A STUDY ON PEDAGOGICAL COMPETENCE OF 2015 PPL STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITY OF RIAU - M. Reza Rahman; Fakhri Ras; M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objective of thisreseach is to acknowledge the ability onpedagogical competence of 2015 practice teaching of (PPL) students of English StudyProgram of FKIP University of Riau. The research is a descriptive research method.This research consists of one variable, that is teachers’ pedagogical competence. It ishoped that this research can be used in motivating students in learning English. Thepopulation of this research is the seventh semester students at English Study Program ofFKIP of University of Riau Pekanbaru and there were 50 students of class A, B and C.The questionnaire of the research cover 28 items about teachers pedagogicalcompetence with 4 options of 7 indicators. Through the questionnaire, the data werecollected and then analyzed by using M. Ali’s (1993) formulae. Based on the dataanalysis, it was found that the English students’ pedagogical competence is in the levelof good. In detail, the most dominant problem faced the students is in interrelationshipamong school, family, community, national education and educational innovation. Theeffort of the English students should be sustained in the part of educational institutions,principals, and teacher in order to improve the quality of the student-teachers’pedagogical competence.Key Words : Pedagogical Competence, Practice Teaching (PPL), and English StudentsAbility in Teaching class.